Burden of Injury From Explosive Remnants of Conflict in Lao PDR and Cambodia. (March 2013) - Durham, Jo; Hoy, Damian
In postconflict settings, a substantial number of injuries and related disabilities are caused by land mines and explosive remnants of war. This article reviews the literature on the prevalence of these injuries and subsequent disabilities in Cambodia and Lao PDR. Three major electronic databases were systematically for publications on the prevalence of these injuries. Six studies met the inclusion criteria. Five of these were in Cambodia and 1 in Lao PDR. None of these studies could estimate national prevalence rates of these injuries; only 2 considered the broader impact of related disabilities. The different methodological approaches and limitations of the studies prevented statistical synthesis. The studies reviewed suggested accurate estimates of the prevalence of war injuries and consequent disabilities are missing. There is a need for a comprehensive epidemiological research to quantify the burden that results from such injuries.